Effect of coffee, tea and alcohol intake on circulating inflammatory cytokines: a two sample-Mendelian randomization study - He, Yuan; Zhu, Shuang; Zhang, Yu; Tan, Chin Ping; Zhang, Jianbin; Liu, Yuanfa; Xu, Yong-Jiang (Springer Nature, 2024)
Background: Despite the abundance of research examining the effects of coffee, tea, and alcohol on inflammatory diseases, there is a notable absence of conclusive evidence regarding their direct causal influence on circulating inflammatory cytokines. Previous studies have primarily concentrated on established cytokines, neglecting the potential impact of beverage consumption on lesser-studied but equally important cytokines. Methods: Information regarding the consumption of coffee, tea, and alcohol was collected from the UK Biobank, with sample sizes of 428,860, 447,485, and 462,346 individuals, respectively. Data on 41 inflammatory cytokines were obtained from summary statistics of 8293 healthy participants from Finnish cohorts. Results: The consumption of coffee was found to be potentially associated with decreased levels of Macrophage colony-stimulating factor (β = −0.57, 95% CI −1.06 ~ −0.08; p = 0.022) and Stem cell growth factor beta (β = −0.64, 95% CI −1.16 ~ −0.12; p = 0.016), as well as an increase in TNF-related apoptosis-inducing ligand (β = 0.43, 95% CI 0.06 ~ 0.8; p = 0.023) levels. Conversely, tea intake was potentially correlated with a reduction in Interleukin-8 (β = −0.45, 95% CI −0.9 ~ 0; p = 0.045) levels. Moreover, our results indicated an association between alcohol consumption and decreased levels of Regulated on Activation, Normal T Cell Expressed and Secreted (β = −0.24, 95% CI −0.48 ~ 0; p = 0.047), as well as an increase in Stem cell factor (β = 0.17, 95% CI 0.02 ~ 0.31; p = 0.023) and Stromal cell-derived factor-1 alpha (β = 0.20, 95% CI 0.04 ~ 0.36; p = 0.013). Conclusion: Revealing the interactions between beverage consumption and various inflammatory cytokines may lead to the discovery of novel therapeutic targets, thereby facilitating dietary interventions to complement clinical disease treatments. © The Author(s), under exclusive licence to Springer Nature Limited 2024.